Ergogenic aids: What athletes are using and why - Eichner, E. R. (The Physician and Sportsmedicine, 1997)
Athletes at all levels explore ergogenic aids. Testosterone and growth hormone are still abused and difficult to detect. Single doses of albuterol or salmeterol do not seem ergogenic, but questions remain about prolonged dosing and about other beta2 agonists. Caffeine can be ergogenic for prolonged or brief exertion. Creatine supplementation is legal and in vogue among strength and power athletes. Not all studies agree, but creatine seems ergogenic for repeated brief bouts of intense exercise. Ergogenic aids pose vexing questions for athletes, physicians, and society.